1995
DOI: 10.1007/bf02752185
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome in relation to mode of delivery in meconium stained amniotic fluid

Abstract: Meconium staining of the amniotic fluid is a common complication during labour. When facilities like electronic monitoring, foetal blood sampling are not available, it is difficult to decide whether labour should be allowed to continue or caesarean section should be done. Even when caesarean section is done, meconium aspiration syndrome (MAS) can still occur and considerable morbidity and mortality may result in the newborn. Amino infusion is being considered as useful in decreasing MAS and its sequelae. Befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…This is because thick meconium tends to occur later in second stage, perhaps during the instrumental delivery. Finding of this study is comparable to the 6 Clifford et al found cesarean section rate of 38% in MSAF group as compared to 26% in clear liquor group. 13 In the present study the association of MSAF with low Apgar was strong, 22.8% of thick MSAF babies had low Apgar score (<5) at one minute as compared with thin MSAF born babies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is because thick meconium tends to occur later in second stage, perhaps during the instrumental delivery. Finding of this study is comparable to the 6 Clifford et al found cesarean section rate of 38% in MSAF group as compared to 26% in clear liquor group. 13 In the present study the association of MSAF with low Apgar was strong, 22.8% of thick MSAF babies had low Apgar score (<5) at one minute as compared with thin MSAF born babies.…”
Section: Discussionsupporting
confidence: 86%
“…Intrauterine asphyxia also produces a gasping response by which meconium enters the trachea and once it has been aspirated into lungs it causes mechanical obstruction to airways, chemical pneumonitis and atelactasis. 6 Approximately 10-20% of live births demonstrate meconium in the amniotic fluid, yet few infants are adversely affected. Therefore the current risks associated with meconium remains uncertain and Gupta SN et al September-December 2012;Vol 10 (No.3);198-202 Maternal & fetal outcome in term labour controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, 75% cases had normal fetal heart rate at the time of detection of meconium, 18% had bradycardia & 7% had tachycardias which were similar with the findings of Berkus et al 8 who observed significantly higher risk of an abnormal fetal heart rate in meconium stained group. Sasikala et al 9 found that 26.2% had fetal bradycardia & 6.5% had tachycardia. In present study, APGAR score in first minute was low (<7) in 5.26% patients with thin meconium as compared to 18.51% of patients with thick meconium.…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic Fluid surrounds the fetus in intrauterine life providing low resistance space suitable for growth and development. (1) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%